Synthesis, molecular docking and heme detoxification of pyrano[2,3-c]pyrazoleaminoquinoline hybrids as potential antimalarial agents - Lekkala Ravindar; Ng, Yan Hong; Khairul Azreena Bakar; Ahmad Fadhlurrahman Ahmad Hidayat; Shevin Rizal Feroz; Raheem, Saki; Siti Aishah Hasbullah; Nurul Izzaty Hassan (Penerbit Universiti Kebangsaan Malaysia, 2024)
Malaria, an infectious disease that spreads widely and can kill people, is still a problem for global health. This study adds to the list of possible solutions by making a group of new pyrano[2,3-c]pyrazole-aminoquinoline hybrids. Here, five novel hybrids were synthesized by covalently linking the scaffolds of 4-aminoquinoline and pyrano[2,3-c]pyrazoles via an ethyl linker. Molecular docking was used to study each hybrid’s and standard chloroquine ability to bind to Plasmodium falciparum lactate dehydrogenase enzyme (PfLDH), an important enzyme in the parasite’s glycolytic pathway. The hybrid compounds had a stronger binding affinity than the standard chloroquine. Compound 4c (-7.79 kcal/mol) and 4d (-7.73 kcal/mol) had strong interactions with PfLDH through hydrogen bonds, hydrophobic interactions, and Van der Waals interactions involving Val-26, Ile-54, Ala-98, Phe-100, Lys-118, Ile-119, and Glu-122. Additionally, the study explored the interaction between five hybrids and hemin, a pivotal component in the heme detoxification pathway of malaria parasites. The isothermal titration calorimetry (ITC) showed that the hybrids had different strengths when binding to hemin. This was because their structures were different. Hybrids 4a and 4b showed a strong affinity for hemin with Ka values of (1.43 ± 0.60) × 106 M-1 and (1.64 ± 0.97) × 106 M-1 , respectively, indicating that they might be able to stop the disruption process. In contrast, hybrids 4c, 4d, and 4e interacted with hemin with markedly lower affinities. This study provides insights into the promising antimalarial properties of pyrano[2,3-c]pyrazole-aminoquinoline hybrids. It details their interactions with PfLDH and hemin and offers potential avenues for developing novel therapeutic strategies against malaria.